Should anonymous’ comments in forum threads be totally disregarded? - Chua, Kun Guan. (2011)
Often in a discussion thread, Anonymous or guests, which are users with no details, can be seen commenting on different topics. As just like talking to strangers, interaction with Anonymous often poses the question on their credibility. The reliability of their comments is often put into question whether they should be considered when doing research on the discussion or should they just be filtered out. The main goal of this project is on the investigation to find out whether the comments by Anonymous can be trusted and therefore safe to include for research. The investigation first started from scratch from the implementation of the extraction, then the cleansing of the thread, putting the data into graph and finally visualization of the network. The implementation required various programming techniques in order to perform various tasks at different portions of the project and various methods were tested for the efficiency to come up with the most efficient method.